Pengaruh Model Pembelajaran Teams Games Tournament Terhadap Keaktifan Belajar IPAS Pada Siswa Kelas IV - Tri Muthiah Utami; Rahmiati Rahmiati (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2024)
Teachers play a crucial role in facilitating a high-quality learning experience for their students by putting learning into practice. For this situation, educators bear a huge obligation in giving a conversation space to understudies to turn out to be more mindful of the improvement of information. This study's goal is to ascertain whether the Teams Games Tournament (TGT) learning model influences the activeness of IPAS learning. A semi exploratory trial plan with a group post-test just plan was utilized for the examination. The investigating technique utilized was a drenched model. The research study used two sample groups: a control group of 22 Class IV A students and an experimental group of 21 Class IV B students. This study gathered data through the use of a questionnaire. The Pearson item second technique was utilized to evaluate the information's legitimacy. Additionally, the Cronbach's Alpha equation was used to evaluate the information's dependability. In the normality test, the Liliefors formula was used and the data was normally distributed, the control class had an importance worth of 0.083, while the exploratory class had an importance worth of 0.102. With an importance level of 0.850 ˂ 0.05, the homogeneity test utilizing the Fisher recipe shows that the information come from a similar populace. The hypothesis test's calculation gave a two-tailed significance level of 0.045. The investigation discovered that 4th grade understudies at SDN Jatiwaringin II Bekasi are more participated in their learning of IPAS subjects while utilizing the TGT learning model.